Reversible disruption of XPO1-mediated nuclear export inhibits respiratory syncytial virus (RSV) replication - Cynthia Mathew (Nature Portfolio, 2021)
Abstract Respiratory syncytial virus (RSV) is the primary cause of serious lower respiratory tract disease in infants, young children, the elderly and immunocompromised individuals. Therapy for RSV infections is limited to high risk infants and there are no safe and efficacious vaccines. Matrix (M) protein is a major RSV structural protein with a key role in virus assembly. Interestingly, M is localised to the nucleus early in infection and its export into the cytoplasm by the nuclear exporter, exportin-1 (XPO1) is essential for RSV assembly. We have shown previously that chemical inhibition of XPO1 function results in reduced RSV replication. In this study, we have investigated the anti-RSV efficacy of Selective Inhibitor of Nuclear Export (SINE) compounds, KPT-335 and KPT-185. Our data shows that therapeutic administration of the SINE compounds results in reduced RSV titre in human respiratory epithelial cell culture. Within 24 h of treatment, RSV replication and XPO1 expression was reduced, M protein was partially retained in the nucleus, and cell cycle progression was delayed. Notably, the effect of SINE compounds was reversible within 24 h after their removal. Our data show that reversible inhibition of XPO1 can disrupt RSV replication by affecting downstream pathways regulated by the nuclear exporter.